Pendapat Pengunjung Terhadap Pengembangan Destinasi Wisata Religi di Kawasan Masjid Agung Semarang Berdasarkan Komponen Pariwisata - Guntur Pamungkas; Hadi Wahyono (Jurusan Perencanaan Wilayah dan Kota, 2022)
Masjid Agung Semarang is one of the main tourist destination in Semarang, this particular destination is social-culture strategic area according to Regional Spatial Plan of Kota Semarang (RTRW) 2011-2031. Eventually to achieve its target as Social-culture Strategical Area, it needs religious tourism development with a tourism component approachment. Generally aspects which affect religious tourist destination are atraction, accessibility, amenity, activity, available packages, and ancillary services. Hence in this research those aspects will be analyzed further more. Besides, participation of tourist to contribute in the assesment of tourism service attributes considered significant. Based on this value of tourist opinion, identification of assesment from the tourist for the religious tourism destination development in Masjid Agung Semarang. Therefore, the goal of this research is to identify tourist opinion regarding the development of Masjid Agung Semarang area as religious tourism destination based on tourism components.